Wave Characteristics of Magnetic Pi2 Pulsations in the Auroral Region: Conjugate Relationships - Kuwashima, Masayuki (1981)
P(論文) Conjugate relationships of Pi2 are studied by using data at Syowa Station in Antarctica and Reykjavik (Husafell) in Iceland. The results indicate an odd-mode hydromagnetic standing oscillation as a main cause of Pi2. The generation mechanism of Pi2 is examined theoretically on the basis of the observational results. departmental bulletin paper